A comparative study of academic literacy in English medium instruction programs in UAE and Finland - Chell Geraldine; Mikkilä-Erdmann Mirjamaija; Iiskala Tuike; Dillon Anna (WESTERN AUSTRALIAN INST EDUCATIONAL RESEARCH INC, 2022)
Graduate students in English medium instruction (EMI) programs face challenges with academic literacy, the fundamental tool for thesis writing. Therefore, this paper investigates the promotion of academic literacy from the perspective of curricula. Aligning with Tardy's (2009) genre knowledge theory and its four genre knowledges necessary for developing academic literacy, this comparative study adopts a socio-cultural position of learning by utilising the knowledges as analytical lenses to explore and compare the documents of two masters programs in the UAE and Finland. Iterative theory and data-driven coding revealed that for both curricula, the intended learning outcomes address these four genre knowledges. However, tacit assumptions of two genre knowledges and possible culture shock concerning the transition from didactic learning to substantial independent study may be barriers for students in EMI settings. In addition, bridging the gap between English language entry requirements and learning outcomes, and fostering community learning environments may better facilitate the realisation of students' full potential.